Steam reforming and indirect partial oxidation of light hydrocarbons over bimetallic catalysts - Gökaliler, Feyza. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
This experimental work involves the investigation of power law type kinetic study of ethanol steam reforming and indirect partial oxidation of propane/n-butane mixture with the purpose of hydrogen production over a bimetallic 0.2wt%Pt-15wt%Ni/?-Al2O3 catalyst. The kinetic investigation of ethanol steam reforming gave reaction orders of 1.18 and -0.18 wrt ethanol and steam, respectively and an activation energy of 39.3 kJ mol-1. IPOX tests were conducted for a hydrocarbon feed of a 1:1 propane/n-butane mixture. The effects of temperature, steam/carbon ratio, carbon/oxygen ratio and residence time were investigated. Hydrogen/carbon monoxide ratio tended to increase with higher steam/carbon, W/FTotal and C/O2 ratios. A decrease in residence time led to a considerable increase in the hydrogen production. The composition that represents LPG fuel in this study, with a propane/n-butane ratio of 1:1, seems to be superior to the previously tested composition, a ratio of 3:1, considering the hydrogen production rate (151 versus 70); and the hydrogen/carbon monoxide ratio (49 versus 46). Optimum activity and selectivity for IPOX of propane/n-butane mixture was obtained with steam/carbon ratio of 7, carbon/oxygen ratio of 2.70 and W/F ratio of 0.51.
Keywords: Hydrogen.; Metal catalysts.; Catalysis.